PENERAPAN MODIFIKASI PERMAINAN BOLAVOLI UNTUK MENINGKATKAN EFEKTIFITAS PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (STUDI PADA SISWA KELAS VIII DI SMP NEGERI 1 GEDANGAN, SIDOARJO) - WAHYU KURNIAWAN, DWI (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract The Implementation of physical education, sport and health is a long term investment. In order to obtain the expected result requires relatively long time. It is certainly needed an action that support the conducive learning. Physical education, sport and health  is one of the subjects which is favored by many junior high school students because the material contains a variety of games that involve direct physic and mental activities so that children become active to follow it. The teacher should provide clear materials to students with delivering such a creative and innovative teaching in order to be more easily understood by students and learning become effective. To deliver creative, innovative and effective teaching is with modifying a lesson in order to make it more interesting, one of them is modify volleyball game. Creative, innovative and effective learning use a dikjasor observation sheet with three observers and from the point of view of students using questionnaires formative class evaluation (FCE). This study aimed to determine the influence of modifies volleyball game on the effectiveness of learning. This research is descriptive quantitative approach experiment with design of the study is a randomized pretest-posttest control-group design. The subjects are 33 students in the experimental group and 33 students in the control group. Generally from the results of research it can be concluded  that there is an influence significated the implementation of modified volleyball game against Penjasorkes learning effectiveness in class VIII in SMP Negeri 1 Gedangan as evidenced by the results of the t test on the same sample tcount 3,339 > 1,990 ttable with significated on 0,05. And than Increase the implementation of modified volleyball game against Penjasorkes learning effectiveness in class VIII in SMP Negeri 1 Gedangan by 5%. Keywords: volleyball game modification, Penjasorkes learning effectiveness.